Solar photovoltaic system based on perturb and observe maximum power point tracking with trapezoidal rule approach under partial shading conditions - Altwallbah, Neda Mahmod Mohammad. (2022)
Photovoltaic (PV) energy has grown enough to be the most popular renewable energy source due its sustainability and advantageous properties. However, the performance of the PV panels is highly sensitive to weather variations and the incident illumination. PV system performance is highly impacted by partial shading conditions (PSCs), The shading affects the pattern of the power- voltage (P–V) characteristic curve to contain more than one power peak, which creates difficulties on extracting the maximum power point (MPP), and hence, the generated power will reduce. Many maximum power point tracking (MPPT) algorithms were proposed in literature, such as conventional and soft computing algorithms. Among all proposed algorithms, perturb and observe (P&O) algorithm is the most popular due to its simplicity and good convergence. However, P&O suffers from considerable oscillation in the output power, and in the original form, P&O is not capable to perform efficiently under PSC, and needs improvement to be prosperous. Several works proposed different modifications on P&O algorithm to handle the main drawbacks, in addition to combine the P&O algorithm with a soft computing algorithm to track global peak under PSC, which is known as the hybrid approach. These improvements presented an enhanced performance, but the performance enhancement comes at the expense of the algorithm simplicity, computational overhead, requirements and tracking speed. Therefore, the proposed work has the main target on improving P&O by three sequenced phases. The first is to introduce a modification in conventional P&O algorithm, to be able to achieve the global maximum power point (GMPP) effectively in the presence of shading conditions. The second is to propose a hybrid MPPT algorithm based on modified P&O algorithm assisted by Extremum Seeking Control (ESC) approach, in order to maximize the extracted PV power under complex PSC. The third is to present a novel P&O GMPP tracking algorithm. Employing trapezoidal rule concept as a new consideration in the P&O tracking process is successful to result a highly efficient approach in extracting the extreme available power from the PV array under PSCs and severe cases of weather fluctuation. The three proposed algorithms are tested under different cases of PSC, considering a comprehensive weather fluctuation such as sudden and fast change in incident radiation levels. The algorithm is validated using two different methodologies: a simulation model in MATLAB/Simulink and hardware implementation. Both simulation and hardware results confirm that the proposed algorithm provides excellent efficiency of 100% and 99.6% respectively. The GMPP is achieved within less than 100 ms, which is extremely advantageous tracking time, that avoids the power losses. In addition, the minimal steady-state oscillation has been achieved, with the desired level of simplicity without the need to complicated computations or random particles. In this research, the performance of the P&O algorithm is gradually improved, starting with modified P&O and progressing to hybrid P&O and finally to a new version of P&O that can be efficiently applicable under PSC as well as under uniform weather conditions.